แนวทางการพัฒนาการจัดระบบสารสนเทศเพื่อการประกันคุณภาพการศึกษา โรงเรียนเสริมงามวิทยาคม อำเภอเสริมงาม จังหวัดลำปาง - พนัชกร ไชยานนท์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this study is to study the problem, suggestion and the developing guidelines for information system management for quality assurance of Soem Ngam Wittayakom School, Some Ngam district, Lampang province. The sample of the study were the committee of Soem Ngam Wittayakom school quality assurance, the committee of basic education, the specialist of information system management, the staff of the school that was successful in information system management, the head of information division of secondary educational service area office 35 and external assessor. The total number of the sample was 60 people. The tool for this study were questionnaires, interview, workshop for making developing guidelines for information system management for quality assurance of Soem Ngam Wittayakom School, Soem Ngam district, Lampang province and check list for the draft of guidelines for developing information system management for quality assurance of Soem Ngam Wittayakom School, Soem Ngam district, Lampang province. The data was analyzed by using frequencies, percentage, median and standard deviation.